Gender diversity in the course of acute coronary syndrome - O. S. Donirova (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
The article presents the results of the analysis of gender differences in patients hospitalized with diagnosis "acute coronary syndrome". The most common risk factor of acute coronary syndrome among men was smoking. The most common risk factors of acute coronary syndrome among women were general obesity, abdominal obesity, arterial hypertension and diabetes. Men significantly more frequently had multiform coronary disease with predominantly proximal level of the pathological process in comparison with women. Men are more often subjected to invasive treatment of acute coronary syndrome.